Guyana : Public Expenditure Review - World Bank (Washington, DC, 2013)
Since independence in 1966, Guyana's economy has gone through a state control of major productive sectors, and financial institutions - including controls of prices, credit, and foreign exchange - to a combination of political/social unrest, with terms of trade deterioration, and slow economic growth. This led Guyana to become the fourth poorest country in the Western Hemisphere, despite its rich endowment in mineral resources, biodiversity, and forested land. In this context, the main objective of the Public Expenditure Review (PER) is to analyze its expenditures so as to gain understanding of the structure of Government's budget processes to allow its execution, and, assist the Government in reorienting policies, institutions, and expenditures, to achieve private sector-led growth, and better services to the poor. The PER identifies a number of weaknesses in the budget process, namely, the need for intermediate steps to set the budget within a forward-looking medium term expenditure framework, the need to prepare current and capital expenditure budgets jointly, planning for future recurrent costs, and, the need to present the budget to Parliament on a timely basis with adequate information. Recommendations suggest the budget be prepared within a national development program, and a multi-year rolling expenditure framework, with integrated budget processes for current, and capital expenditures, and, strengthening the capacity of the Ministry of Finance for economic modeling, and forecasting. The report assesses sectoral policies, and expenditures in four broad areas: health, education, poverty programs, and infrastructure, focusing on how policies, incentives, and budgetary allocations can change to improve economic efficiency, and poverty alleviation.